Ambient media - innowacyjne działania i narzędzia komunikacji marketingowej - Hall, Hanna; Gębarowski, Marcin (Ambient Media - Innovative Tools and Activities of Marketing Communication, 2006)
The authors have presented the essence of the "ambient media" issue, as well as factors which make entrepreneurs agree to use non-standard solutions in the area of marketing communication. A special attention has been put to carriers and activities which are most often used while carrying out original marketing actions - marketing events, non-standard outdoor campaigns and buzz marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 82-89